The Effect of Air Flow and Stirring Frequency in Continuous Thermophilic Composting - Rochaeni, Anni; Ariantara, Bambang; Mulyatna, Lili; Nugraha, Arief; Apriansyah, Riza (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
Continuous Thermophilic Composting (CTC) was developed as a modification of continuous composting carried out in the thermophilic phase, where the organic waste degradation process runs quickly. Previous CTC research used lamps as a heat source, which was then changed to use a heater. Several important factors in composting are stirring and air circulation to increase oxygen levels so that the aerobic composting process occurs. The machine has been modified by making air holes and setting automatic stirring. This research aims to determine the air hole openings and stirring frequency that provide the best results. The research was carried out in 2 stages. The first stage is to look for air hole openings with 3 variations: closed, half open, and fully open. Continue by finding the best stirring frequency with 3 variations: once a day, 2 times a day, and 6 times a day. The parameters measured include temperature measured humidity and pH during the composting process, and chemical analysis of fresh waste, compost starter, and mature compost resulting from the process. The research was carried out for 8 days with the addition of 1 kg of artificial waste per day. The results showed that half-open air holes produced better compost quality and temperature consistency in the thermophilic phase. And the stirring frequency of 2 times a day produces consistent temperature results in the thermophilic phase and compost quality that meets SNI 19-7030-2004 of Compost Specifications from Domestic Organic Waste.